Interconnectedness and Contagion Effects in International Financial Instruments Markets - Igor Kravchuk (Montenegrin Journal of Economics, 2017)
The aim of the research is to define possible contagion level of capital market resulting from shocks in main international stocks and bonds markets on basis of the assessment of market interconnectedness. Global Vector Autoregressive model was built up for securities markets in China, Euro area, Japan and the U.S. Using generalised impulse response functions scenarios of influence of shocks in market and estimate of contagion level in selected time horizon are simulated.